Evaluating healthcare learning in virtual reality: a systematic review - Silva, Vitor Dos Santos; Nunes, Fátima L. S. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Virtual Reality (VR) is increasingly employed in healthcare training because it can create interactive three-dimensional learning environments that minimize risk to patients. As VR-based educational interventions become more widespread, evaluating their learning outcomes is becoming a critical focus for researchers and practitioners alike. Although there are a few other studies which verified VR learning in healthcare, they had as their subject the effectiveness of VR itself, not the methods which are used to evaluate learning. This systematic review examined 72 studies (selected from an initial pool of 22773 retrieved from IEEE Xplore, Scopus, Springer, ACM, and PubMed) that span a range of healthcare domains, with a primary focus on surgery and rehabilitation. The studies demonstrated a broad diversity of evaluation methods, including objective measures, subjective questionnaires, and AI-assisted assessments. While the overall methodological quality was generally high, the significant variability in evaluation approaches creates challenges for cross-study comparison and synthesis. The findings underline the necessity for validated, VR-specific assessment frameworks to facilitate the development and expansion of VR applications in lesser-explored areas of healthcare education.